457-nm radiation source based on a diode laser for precision spectroscopy of magnesium atoms. (March 2020) - Goncharov, A.N.; Baraulya, V.I.; Bonert, A.E.; Tropnikov, M.A.
Abstract: We report on the development of a highly stable source of 457-nm radiation based on a diode laser and a tapered amplifier operating in a double-pass scheme. The diode laser frequency was stabilised by a high- Q reference Fabry – Perot interferometer and doubled in a PPSLT nonlinear crystal placed in an enhancement cavity. At a maximum output power of 200 mW at a wavelength of 457 nm, the laser linewidth was less than 5 kHz. The radiation source operation was demonstrated in experiments on precision spectroscopy of cold magnesium atoms in a magneto-optical trap.